The eastern Palearctic species of Agnetina (Plecoptera: Perlidae) - Sivec, Ignac (Scopolia, 2005)
Seven Agnetina species known from the eastern Palearctic region are redescribed from types and from newly associated material. Illustrations of male and female genitalia, head and pronotal patterns, eggs, larval color patterns and larval proventriculi are used to support species descriptions. Perla cadaverosa McLachlan and P. immersa McLachlan are transferred to Agnetina, a female lectotype is designated for A. cocandica (McLachlan) and A. dubia Zwick is placed as a synonym of A. pedata (Koponen). Preliminary keys are presented for adults and larvae.
Keywords: insekti; Plecoptera; Perlidae; Agnetina; zoogeografija